CHARACTERIZATION OF CAPSULE MORPHOLOGIC PROPERTIES AND ALKALOID CONTENTS OF TURKISH POPPY GENOTYPES WITHIN ANKARA ENVIRONMENTAL CONDITIONS - Yagmur Kahraman Yanardag; Sibel Day; Nilgun Bayraktar (Journal of Animal and Plant Sciences, 2024)
Poppy (Papaver somniferum) L. is cultivated commercially in several countries legally to produce alkaloids (i.e. morphine, codeine, thebaine, narcotine, papaverine and oripavine) for pharmaceutical industries. The demand for these alkaloids is increasing and Global climate change is influencing poppy cultivated areas. Türkiye is responsible for poppy cultivation, breeding new cultivars and adaptation trials. Therefore, the present investigation was undertaken during two years to examine the most cultivated 16 cultivars and 3 new lines for capsule morphology properties, their alkaloid values and capsule yield in Ankara conditions which is not in the poppy cultivation area in Türkiye. The experiment was arranged in the randomized complete block design with four replications. The plot size of 2.4 m² (2 m × 1.2 m) and 4 rows with spacing 30 cm between rows and 10 cm within plants were applied. The capsule parameters and alkaloid content were measured in 10 dry capsules after harvesting. To measure the content of alkaloids (%) the capsules were ground into powder and HPLC-MS/MS analysis after the solvent extraction of poppy straw on dry matter was conducted. Genotypes showed variation in stigmatic rays and the number of stigmatic rays was higher in the first year. The maximum stigmatic ray value was seen in cv. Ofis-95 with 13.27 in the first year. The maximum value for capsule length and diameter was obtained from cv. Ofis-NP (51.75 mm) and cv. Ofis-95 (45.00 mm) in the mean of two years. The maximum capsule yield was obtained from cv. Ofis-95 for both years and the values were 155.90 and 160.30 kg daˉ¹. The maximum morphine percentage was recorded in cv. Ofis-1 with 1.63 and 1.24% respectively. The percentage of noscapine, codeine, thebaine was noted as maximum values in Ofis-1 among genotypes. The results favoured the cultivation of these genotypes in Ankara which is not one of the poppy cultivation area and further agronomic studies should be undertaken to develop production technology of poppy in these environmental conditions.
Keywords: Papaver somniferum; cultivation; capsule yield; morphine; noscapine